"Hot Cord" Sign on 18F-FDG PET/CT in a Patient With Acute Myelitis Due to Neuromyelitis Optica Spectrum Disorder. (January 2021) - Alkhaja, Maryam Ahmed; Cheng, Lenith Tai Jit; Loi, Hoi Yin; Sinha, Arvind Kumar
Abstract : Abstract: A 44-year-old woman presented with prolonged low-grade fever, bilateral upper limb weakness, and hyperesthesia. MRI showed hyperintense T2 signal and enhancement of the cervicothoracic spinal cord. 18 F-FDG PET/CT was requested to investigate pyrexia of unknown origin. It demonstrated diffusely increased FDG uptake along the entire spinal cord, suggestive of extensive acute myelitis. Initial blood work was positive for antinuclear antibodies and anti-Ro/SSA antibodies. Cerebrospinal fluid analysis revealed lymphocytosis and detected the presence of neuromyelitis optica aquaporin-4–immunoglobulin G antibodies, fulfilling the criteria for diagnosis of neuromyelitis optica spectrum disorder.